Psychosocial Predictors of Wellness in College Students. Issue 1 (10th April 2018) - Robino, Ariann; Foster, Thomas
Abstract : The authors examined how the first 6 stages of psychosocial development predict wellness in undergraduate college students using the Measures of Psychosocial Development (Hawley, 1988 ) and the Perceived Wellness Survey (Adams, Bezner, & Steinhardt, 1997 ). Results indicated that 4 of the 6 stages predict wellness in college students. Clinical implications for counselors of this population are provided.